Pengaruh Digital Marketing dan Kualitas Produk Terhadap Loyalitas Pelanggan Pada Khalifa Muslim Wear - Rita Kusumadewi; Budi Rusdian (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
In the new era of marketing, companies are forced to be able to create consumer value because today's marketing is driven by values. The purpose of this paper is to analyze the value using the House of Quality (HOQ) matrix which is one of the tools of Quality Function Deployment (QFD) which is commonly used to increase value through product attributes that will be given to consumers. Equipped with a matrix that illustrates how to create value using HOQ, using data from research that the author has previously carried out in identifying consumer values ​​at private universities in Region III Cirebon-West Java as an example.This research uses explanatory survey method with cross sectional development method. The iteration method is used to determine the number of samples, so that a minimum sample of 116 is obtained, but 150 samples will be used so that the results are more representative of the population. The result shows that the indicator that is considered the most important by the respondents is the reputation of the university and the indicator with the lowest rating is the time of completion of studies. However, the results of consumer assessments regarding customer value indicate that the university's reputation is still unable to provide superior customer value. Thus, the reputation of the university is an aspect that must be improved first before other aspects.